Litsa vlasti . Litsa vlasti . Faces of Power . Лица власти - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the fight against corruption, in particular, corruption in the activities of the "Vozhrozhdeniie" ("Renaissance") foundation Featured in the program: Makarov, Andrei Mikhailovich (Head of the Directorate of the Struggle with Organized Crime under the Russian Security Council); Il'iushenko, Aleksei Nikolaevich (Head of the Control Directorate of the Presidential Administration of the Russian Federation) Contributors: Nosovets, Sergei (Anchor) Обсуждение проблемы борьбы с коррупцией; в частности, коррупцией в деятельности фонда „Возрождение.“. В программе участвуют: Макаров, Андрей Михайлович (Начальник Управления по обеспечению деятельности Межведомственной комиссии Совета Безопасности РФ по борьбе с организованной преступностью и коррупцией); Ильюшенко, Алексей Николаевич (Начальник Контрольного управления Администрации Президента РФ) Создатели: Носовец, Сергей (Ведущий/Ведущая)